Corrupção na Lava Jato: desvio individual ou mal social? Uma análise das representações pela mídia na perspectiva da LSF - Freitas, Jéssica Cantele de (2017)
This paper aims to investigate the representations of the term “corruption” in Operation Lava Jato contexts, using a contextual, lexicogrammar and semantic-discursive perspectives. To do such, theoretical principles of Systemic Functional Linguistics were used, specifically, the transitity system (HALLIDAY; MATTHIESSEN, 2014), Appraisal (MARTIN; WHITE, 2005) and as well as the representation of social actors (VAN LEEUWEN, 1997). The corpus of this research is composed of twenty (20) texts, whose main topic is the Operation Lava Jato and that present the term “corruption” at least four times. Such texts, available at Observatório da Imprensa, were published between March 2014 to August 2016 and were written by various authors. The methodology adopted is comprised of two stages: contextual analysis and linguistic analysis. The former consists of identifying the context of culture and the context variables of each text. The latter regards the linguistic analysis, unfolded as it follows: a) selection of clauses that present the term “corruption” and its referents; b) transitivity system analysis, in order to prove the representation of the role played by the term “corruption”; c) analysis of Appraisal to identify the evaluative representations; d) representations of social actors analysis, so that one can identify if the term is represented actively or passively; e) semantic systematization and categorization of the results. Such results showed representations to “corruption” that can be grouped into ten (10) semantic categories: it is; actions related to it; consequences; those involved; those affected; origin; feelings triggered by it; actions as consequences of it; attitudes to its end; and motive. One can conclude that “corruption” is approached in many ways. However, as to the character of those involved, the majority of the representations related to the phenomenon of corruption is neither individual nor social, it is of institutional character and it is intrinsic to the political system.